Otorhinolaryngological Problem in Geriatric Population - Pyakurel, Manita; Bhatta, Rishi; Pokharel, Rais (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: The main objective of the study was to identify various geriatric  otolaryngological problems in mid western part of Nepal.Materials and methods: A cross-sectional descriptive hospital based study was done from 1st January 2014 to 1st September 2014 among the all patients 60 years or above visiting the outpatient department of ENT/Emergency department of Nepalgunj Medical College. Data collection was done via interviewing with semi structured Performa with questionnaire. Data was entered in SPSS 17th version and exercised the analysis.Results: Among the total 866 geriatric population, female were 450 while 416 were male. Age ranged from 60 to 96 with average age of 70.3 years. Maximum numbers of elderly were of 60-70 years. Farming was the most common occupation in past. Sixty one percent (289) were smokers or tobacco chewer and 23% (106) consumed alcohol regularly. Majority of elderly had Hypertension as main co morbid condition. Decreased hearing was major complaint (82.6%) which was present for on an average 10.5years. Second leading ear problem was tinnitus (47.7%). Regarding nasal problems, bleeding nose was commonest (21.5%) followed by equal proportion of decreased smelling and nasal blockage (16%, 16.2%). Snoring was the frequent throat problem (58.4%) with average duration of approximately 6 years, followed by day time somnolence (16.6%).Conclusion: Among the ENT problems, hearing problem was the most common problem of these elderly. Nasal bleeding was common nasal problem presented among approximately one fourth of elderly. Among the throat problem snoring was the most prevailing with more than fifty percent occurrence. Occasional aesthetical complaint is very common. Head and neck malignancy was least common in these aged populationsNepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, Page: 23-25